Chemical characteristics of Middle Permian formation water and hydrocarbon preservation conditions in Northwest Sichuan. Issue 1 (November 2020) - Yang, C L; Xie, Z Y; Pei, S Q; Guo, J Y; Zhang, L; Dong, C Y; Hao, A S; Yang, C X; Liu, Z X
Abstract: The analysis of the chemical characteristics of the Middle Permian formation water in 10 wells in the northwest of Sichuan Basin indicates that: the TDS of the Middle Permian formation water in Northwest Sichuan increases longitudinally with the burial depth of the formation, and the formation water is mainly of CaCl2 type (Surin classification), Cl-Na-Ca type and Cl-Ca-Na type (Shukarev classification). The rNa + /rCl − and rSO4 2- *100/rCl − of the formation water are 0.05-0.95 and 0-5 respectively, reflecting strong water-rock interaction and strong sealing conditions. The analysis of the chemical characteristics of formation water and the preservation conditions of oil and gas shows that the overall preservation conditions of the Middle Permian in Northwest Sichuan are good, most of which is located in the "preservation zone"; longitudinally, the preservation conditions of Qixia Formation are better than those of Maokou Formation; areally, the preservation conditions of Shuangyushi and Jiulongshan regions are good; the sealing property of the strata in Hewanchang region is poor.